LE VOYAGE D’AFFAIRES – ENJEUX ACTUELS ET FUTURS DANS UNE PERSPECTIVE DIDACTIQUE (BUSINESS TRAVEL – CURRENT AND FUTURE STAKES FROM A DIDACTIC PERSPECTIVE) - Andra-Teodora PORUMB; Adina SĂCARA-ONIŢA (Annals of the University of Oradea: Economic Science, 2024)
In the context of the changes caused by scientific and technical progress, taking into account the demands of speed, promptness, immediate response, attention to details, efficiency, creativity and performance that international business entails, the health crisis of 2020 but also the possible occurrences of other crises of any kind, in recent years there have been changes in the organization and running of the gainful activity and professional travel, which has led to the evolution of the tourist discourse and its themes, to technological and linguistic innovations. In terms of business travel, new internet-connected workspaces have emerged that allow today’s business people to track business, intervene in real-time and continuously participate in transactions from the very first moment of the trip. Also, organizing and planning a trip involves accessing online booking platforms and selecting an extensive range of suitable accommodations or restaurants. In this paper, we will show that, in foreign language courses for business, the use of authentic print and online media documents that present the new realities, in addition to the units dedicated to business trips in textbooks published in the last 20 years, can contribute to updating and expanding the horizons and skills of the students from the Faculty of Economic Sciences, diversifying the contents, means and methods of learning, enriching the vocabulary, to a better understanding of the current economic context.